The increased carbon storage changes with a decrease in phosphorus availability in the organic paddy soil - Suphathida Aumtong; Chakrit Chotamonsak; Bundit Somchit (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2022)
This study aimed to investigate the effect of organic rice farming on the various forms of inorganic phosphorus, the concentration of dissolved organic carbon (DOC) and carbon storage, and the relationship between DOC and P fractions in organic rice farming (ORF). The soil samples were taken from 11 organic plots, and three pseudo-replicates were sampled from individuals of various soil depths. The P-fractions, the soil organic carbon (SOC), DOC, and other soil properties were analyzed by standard methods from soils. The data were analyzed using One-way and Two-way ANOVA and tested using the least significant difference. The results showed that ORF soils had less labile P than conventional rice farming, while ORF had a higher average of DOC, SOC, and C stock than conventional rice soil (P<0.05). Organic fertilizers such as animal manure application and rice straw retention were used for ten years in the ORF. The agricultural practices of ORF would convince the amount of amorphous Fe and Al on soil minerals significantly and would increase the adsorption capacity of the soil mineral surfaces by organic fertilization. The Fe-P fraction responded to the increased adsorption capacity in the ORF and shown along with the DOC and P which were less than in ORF. Both of them were more adsorbed on the surface mineral. Meanwhile, the lower P for nutrient cycling in ORF soil, the lesser the decomposition of DOC and SOC, which then affected the increase of soil C storage.